"But let justice roll down like waters, and righteousness like an ever-flowing stream" (Am 5:24). Social justice versus cult criticism in Amos (5:21–24) and Isaiah (1:10–20): A trauma perspective - Groenewald, Alphonso (HTS teologiese studies, 2019)
The focus of this article is on the cult-critical statement(s) in Amos (5:21–24) and Isaiah (1.10–20). The title of this article inevitably leads us to the question of the relationship between the practice of the cult on the one hand and ethics on the other hand, namely the ‘either–or’ dilemma which exegetes face in the interpretation of these texts. This article should therefore be seen as part of the on-going debate of the significance of the prophetic understanding of the role of the cult versus Israel’s ethical considerations. Furthermore, an overview of important insights from trauma studies, which are applied to the cult-critical statements in the books of Amos and Isaiah, is given.